EPISTEMOLOGI DALAM ILMU TEOLOGI DAN IMPLIKASINYA TERHADAP PEMAHAMAN KEPERCAYAAN DAN KEBENARAN - Onesiporus Lase; Herlina Lende (EUNOIA Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This article explores theological epistemology in relation to modern philosophical epistemology, particularly the traditions of empiricism and rationalism. The encounter between philosophy and theology generates epistemological tensions regarding the source, validity, and authority of knowledge. Using a qualitative approach with content analysis, this study highlights how theological knowledge, while distinct, can still engage in dialogue with modern scientific paradigms. The findings indicate that theological knowledge is not merely rational and empirical but also relational, transcendental, and communal, grounded in divine revelation and the authority of Scripture. This article contributes by offering a critical synthesis between philosophy and theology and proposing the development of a contextual and relevant theological epistemology for both faith practice and contemporary academic discourse.